The Role of Spiritual Leadership in Improving Organizational Citizenship Behavior (OCB) of Islamic Bank Employees - Rakhmaan habibi; Ahmad Syahni; Syafiul Umam (LPPM STIES BABUSSALAM, 2026)
This study aims to analyze the role of spiritual leadership in improving employees' Organizational Citizenship Behavior (OCB) in Islamic banks. Spiritual leadership is a leadership approach that integrates spiritual values, such as honesty, trustworthiness, compassion, exemplary behavior, and worship orientation in organizational activities. The implementation of spiritual leadership is believed to be able to create a meaningful work environment, increase intrinsic motivation, and build employee commitment and loyalty to the organization. This study uses a quantitative approach with a survey method on Islamic bank employees. Data collection was carried out through distributing questionnaires using a Likert scale, then analyzed using simple linear regression analysis to test the effect of spiritual leadership on OCB. Indicators of spiritual leadership include vision , hope/faith , and altruistic love , while indicators of OCB include altruism , conscientiousness , sportsmanship , courtesy , and civic virtue . The results of the study indicate that spiritual leadership has a positive and significant effect on employees' Organizational Citizenship Behavior. The higher the level of spiritual leadership implemented by leaders, the higher the tendency of employees to demonstrate voluntary behavior outside of formal duties, such as helping coworkers, maintaining a harmonious work environment, actively participating in organizational activities, and demonstrating loyalty to the institution. These findings indicate that spiritual leadership is a strategic factor in building a productive, collaborative, and Islamic-based organizational culture. Therefore, Islamic banks need to optimize the development of spiritual leadership as part of their human resource management strategy to continuously improve the quality of individual and organizational performance.